1% Isoflurane and 1.2 μg/ml of Propofol: A Combination of Anesthetics That Causes the Least Damage to Hypoxic Neurons - Bu, Xinyue; Li, Tang; Guo, Di; Yang, Chenyi; Wang, Jinxin; Wang, Xinyi; Yang, Zhuo; Wang, Haiyun (Frontiers in Aging Neuroscience, 2020)
Backgrounds: Aging-related impairment of cerebral blood flow regulation leads to the disruption of neuronal micro-environmental homeostasis. Anesthetics should be carefully selected for aging patients since they have less cognition capacity. Effects and mechanisms of propofol or isoflurane have been widely investigated. However, how different combinations of propofol and isoflurane affect neurons and the mechanism still needs to be demonstrated. Methods: We cultured rat hippocampal neurons and established a hypoxic injury model to imitate the micro-environment of aging brains. Three different combinations of propofol and isoflurane were applied to find out an optimum group via Cell Counting Kit-8 (CCK8) assay, lactic acid dehydrogenase (LDH) assay, real-time qPCR, and immunofluorescence of key proteins. Then BiP was silenced by small interfering RNA (siRNA) to explore the mechanism of how isoflurane and propofol affect neurons. Endoplasmic reticulum (ER) stress was measured by Western blot and immunofluorescence. To detect GABAAR α1 subunit proteostasis and its function, real-time qPCR, immunoprecipitation, and Western blot were carried out. Results: Hypoxic neurons showed no different changes on cell viability, LDH leakage, and ER stress after treatment with 1% isoflurane and 1.2 μg/ml of propofol. Hypoxic neurons showed a sharp increase of LDH leakage and ER stress and a decrease of cell viability after treatment with 1.4% isoflurane and 0.6 μg/ml of propofol or 0.5% isoflurane and 1.8 μg/ml of propofol. After knockdown of BiP, the application of 1% isoflurane and 1.2 μg/ml of propofol led to the decrease of GABAAR α1 subunit protein content and viability of cell, as well as aggravation of ER stress. Conclusion: A combination of 1% isoflurane and 1.2 μg/ml of propofol causes the least damage than do other dosages of both two drugs, and endogenous BiP plays an important role in this process.